IMPROVING FINANCIAL MARKETING AND ACCOUNTABILITY WITH TECHNOLOGY PENETRATION FOR THE BAG SMEs COMMUNITY IN GRESIK, JAWA TIMUR - Hari, Yulius; Dewi, Lily Puspa; Santi, Chitra; Sembiring, Murpin Josua (Advances in Social Sciences Research Journal, 2018)
Micro and small and medium enterprises (MSMEs) contribute greatly to economic growth in East Java. Around 53.4% of economic growth comes from MSMEs, most of which are handicraft industries, one of which is a bag and wallet craftsman (Disperindag East Java, 2016). In its development, MSMEs often experience obstacles in adopting a new technology. Gresik is not only known as an industrial area in East Java, but also has a large potential for MSMEs, one of which is bag craftsmen at Ds. Bedilan, Gresik. In line with government programs related to the development of small and medium-sized industries, this community service activity tries to develop capabilities and technology transfer between universities and the community. As a partner in this service activity is a bag craftsman community which is a micro-scale industry. The main problem raised in this activity is the development of marketing by using information technology and improving financial accountability. In the financial problems that often occur in partners is the frequent mix of cash flow of business units with personal and accounts receivable that are often uncollectible. From the results of this activity it can be concluded that partners have a desire to use good technology, but still have not provided positive results for the perception of ease of use.